2019
DOI: 10.1111/nrm.12237
|View full text |Cite
|
Sign up to set email alerts
|

A copula‐based index for drought analysis in arid and semi‐arid regions of Iran

Abstract: The copula functions are frequently used by researchers for modeling dependence structure among the correlated attributes in many areas. The copulas are widely used for the analysis of drought frequency, drought characteristics, drought coincidence risk, uncertainty, and drought forecasting. In this research, we have compared two indices of drought assessment, including SPI‐12 and copula‐based joint deficit index (JDI). In this regard, the drought characteristics, including the severity, duration, and drought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
1
10
0
3
Order By: Relevance
“…It is concluded that these results are in agreement with Ghadami et al (2020) that identified four homogenous regions of drought severity-duration index at SPI-12 over Iran using 56 stations. Furthermore, based on the results of the Bazrafshan et al (2020), three homogeneous regions of drought in arid and semi-arid areas of Iran can be recognized that confirms the given results of Table 2.…”
Section: Clustering Of Drought Characteristicssupporting
confidence: 84%
See 1 more Smart Citation
“…It is concluded that these results are in agreement with Ghadami et al (2020) that identified four homogenous regions of drought severity-duration index at SPI-12 over Iran using 56 stations. Furthermore, based on the results of the Bazrafshan et al (2020), three homogeneous regions of drought in arid and semi-arid areas of Iran can be recognized that confirms the given results of Table 2.…”
Section: Clustering Of Drought Characteristicssupporting
confidence: 84%
“…Recently, Iran has experienced several drought events, that were addressed by many studies. For instance, studies conducted by Amirataee et al (2018), Bazrafshan et al (2020), Ghafori et al (2020), andNickravesh et al (2020) have been carried out either for several regions of Iran or with respect to the low amount of stations, while only the drought severity during a specific time frame is addressed. However, extensive analysis with respect to spatiotemporal characteristics of drought at different time scales has not been conceded across Iran.…”
Section: Introductionmentioning
confidence: 99%
“…In order to identify extreme events, two indicators were used: standardized precipitation index (SPI) and standardized runoff index (SRI). The SPI was developed by Mc-Kee et al [34] to assess meteorological drought and has been used by many authors [35][36][37]. The SRI was developed on the basis of the SPI concept for the characteristics of hydrological drought [38][39][40][41][42].…”
Section: Methodsmentioning
confidence: 99%
“…After recognizing the characteristic variables of drought events based on the run theory, it is useful to combine the drought characteristic variables with the copula function to analyze the multivariate probability characteristics of drought events (Mirabbasi et al 2012;Kao & Govindaraju 2019;Wang et al 2020). Copula, as a joint function, provides an effective method for multivariate frequency analysis and can model the structure of dependencies among variables (Fan et al 2017;Bazrafshan et al 2019;Lindenschmidt & Rokaya 2019). The copula function can combine multiple drought characteristic variables, which is widely used in hydrological and meteorological fields (Lee et al 2013;Xu et al 2015;Vyver & Bergh 2018;Dash et al 2019).…”
Section: Introductionmentioning
confidence: 99%